Clinical findings and outcome in feline tetanus: a multicentric retrospective study of 27 cases and review of the literature - Dussaux, Alice; Fuhrer, Laurent; Dorner, Martin B.; Santifort, Koen; Vanhaesebrouck, An; Menchetti, Marika; Danciu, Cecilia-Gabriella; Dutil, Guillaume; Escriou, Catherine; Blot, Stephane; Gutmann, Sarah; Taestensen, Carina; et al. (Frontiers in Veterinary Science, 2024)
Tetanus is a toxigenic illness caused by the action of Clostridium tetani neurotoxin (TeNT), which results in partial or generalized muscle stiffness in infected mammals and birds. The disease is rarely reported in cats due to their innate resistance to the toxin. This multicentric retrospective study aimed to describe a significant population of cats with a diagnosis of tetanus and report their signalment, clinical and neurological signs, diagnostic findings, treatment, and outcome. A retrospective search through medical records from eleven referral centers in Europe resulted in the identification of 27 cases of feline tetanus from July 2005 to April 2023. These cases were further compared with previously reported cases in the veterinary literature. Young cats were more commonly represented than older cats, with a median age of 4 years. Clinical signs were initially characterized by a lame and/or stiff limb, near the primary injury site, in 17/26 (65%) cats. Signs were focal or multifocal in 21/27 (78%) cats of this study and one typical sign was the inability to flex the most severely affected limbs. Electrodiagnostic studies revealed characteristic changes, such as continuous spontaneous motor unit discharges in both agonist and antagonist muscles. Such studies are particularly useful in focal and multifocal cases and should be performed to further support the diagnosis. The toxin was successfully identified in one case using the mouse bioassay. Treatment included antibiotherapy (metronidazole) in most cases, muscle relaxants, appropriate nursing cares and handling of potential complications. Overall, the outcome appeared to be positive, with only 1/27 (3. 7%) cats being euthanized due to financial restrains. 23/25 (92%) cats returned to an independent ambulatory capacity on all limbs within a median delay of 25 days. Mild to moderate long-term sequelae were reported in eight (30%) cats. This multicentric study is the first to bring together such a large number of cats affected with tetanus. Presentation of the disease in cats differs from that observed in humans and dogs, with most cats being locally affected. Compared to previous reports of tetanus, this series of cats had a better outcome overall, especially for cats affected with generalized tetanus.